An investigation of oxidation/hot corrosion-creep interaction at 800 °C in a Ni-base superalloy coated with salt mixture deposits of Na2SO4-NaCl-NaVO3. (February 2019) - Mannava, Venkateswararao; Sambasivarao, A.; Paulose, Neeta; Kamaraj, M.; Kottada, Ravi Sankar
Graphical abstract: Highlights: Oxidation/hot corrosion-creep interaction study of Nimonic263 with 3SMs at 800 °C. 3SM is more detrimental than 3SM-A, so lesser rupture time with 3SM than with 3SM-A. Oxides and sulphides preferred to form along the crack regions than on surface. 3SMs accelerate the SAGBO mechanism as well as trigger the intragranular oxidation. Sulphidation followed by oxidation at 250 MPa, and SAGBO at 215&180 MPa are dominant. Abstract: Creep-rupture behaviour of Nimonic263 alloy coated with 87.5 wt.%Na2 SO4 +5 wt.%NaCl +7.5 wt.%NaVO3 (3SM) and 74 wt.%Na2 SO4 +21.7 wt.%NaCl+4.3 wt.%NaVO3 (3SM-A) was investigated in the stress range of 180–350 MPa at 800 °C. The 3SMs are responsible for the reduction in creep-rupture life. Hot corrosion products found in the crack regions of the crept specimens deformed under the influence of 3SMs. Sulphidation followed by oxidation was dominant at 250 MPa, whereas oxidation was dominant at 215 and 180 MPa. Comprehensive microstructural characterization and analysis suggest that three-salt mixtures(3SMs) accelerate oxygen and sulphur penetration along the grain boundaries during creep, and enhance the stress assisted grain boundary oxidation resulting in a reduction in creep-rupture life.